Współpraca państw UE w realizacji polityki akwenowej na przykładzie pierwszej, morskiej, militarnej operacji EUNAVFOR ATALANTA - Pająk, Krzysztof (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
The uncontrollable outbreak of piracy attacks off the Somali coast has lately made the East African coast the area where the majority of all global maritime crimes occur. Located in East Africa, Somalia borders one of the most important maritime communication routes on Earth: the Suez Canal – the Red Sea – the Gulf of Aden. EU states could be acutely affected by the disruption of sea trade in this area, therefore they have become actively involved in fighting piracy off the Somali coast. As a result of political, organizational and legal activity, the Council of the EU established the first maritime military operation under the auspices of the European Union – EUNAVFOR Somalia – Operation Atalanta. The efficient operation of EU naval forces, hundreds of miles from European shores would not have been possible had it not been for an extensive and comprehensive maritime policy. Not only has its implementation enabled the EU to chase pirates in the Somali basin, or helped bring any criminals detained before the courts, but is has also influenced countries outside the European Union.